Effectiveness and Safety of an Inactivated Enterovirus 71 Vaccine in Children Aged 6–71 Months in a Phase IV Study. (17th November 2019) - Guan, Xuhua; Che, Yanchun; Wei, Sheng; Li, Shaoping; Zhao, Zhimei; Tong, Yeqing; Wang, Lei; Gong, Wensheng; Zhang, Ying; Zhao, Yanting; Wu, Yang; Wang, Siquan; et al.
Abstract: Background: Evaluation of a licensed inactivated enterovirus type 71 (EV71) vaccine is needed in a phase IV study with a large population to identify its effectiveness and safety for further application. Methods: An open-label, controlled trial involving a large population of 155 995 children aged 6–71 months was performed; 40 724 were enrolled in the vaccine group and received 2 doses of inactivated EV71 vaccine at an interval of 1 month, and the remaining children were used as the control group. The EV71-infected cases with hand, foot, and mouth disease were monitored in the vaccine and control groups during a follow-up period of 14 months since the 28th day postinoculation through the local database of the Notifiable Infectious Diseases Network. The effectiveness of the vaccine was estimated by comparing the incidence density in the vaccine group versus that in the control group based upon EV71-infected patients identified via laboratory testing. In parallel, the active and passive surveillance for safety of the vaccine was conducted by home or telephone visits and by using the Adverse Event Following Immunization (AEFI) system, respectively. Results: An overall level of 89.7% (95% confidence interval, 24.0–98.6%) vaccine effectiveness against EV71 infection and a 4.58% rate of reported adverse events were observed. Passive surveillance demonstrated a 0.31% rate of reported common minor reactions. Conclusions: The clinical protection and safety of the EV71 vaccine were demonstrated in the immunization of a large population. Clinical Trials Registration: NCT03001986. Abstract : The open-label and controlled phase IV trial involving a large population of 155 995 children aged 6–71 months for long-term observation of 14 months demonstrated a vaccine effectiveness of 89.7% (95% confidence interval, 24.0–98.6%) and good safety.